Analisis Ukuran Perusahaan, Profitabilitas, Solvabilitas Dan Ukuran Kap Terhadap Audit Delay (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di Bei 2013-2015) - RIKNA MUKTI, SUSI (2017)
The study aimed to analyze the company size, profitability, solvency and firm size audit delay in manufacturing companies that is listed on the stock BEI 2013-2015. The population used in this study are a manufacturing company listed on the BEI during the period 2013-2015. The sampling technique used purposive sampling technique. Samples numbered 34 of the companies that are listed on the BEI in 2013-2015, so that the research data was analyzed totaled 102. The data analysis technique that are used are statistical description, classic assumption test and multiple regression analysis to test the coefficient of determination, test F and test t. This study has shown that the coefficient of determination obtained a value 0,242 means that 24,2% audit delay is affected by the variable fiem size, profitability, solvency and firm size. 75,8% while the rest is explained by other variables outside the research model. Hypothesis test result indicate that the solvency and firm size significantly influence audit delay, while the size of company and profitability does not affect the significance to audit delay.